Analysis determinant of poverty in the Barlingmascakeb regionalization: A panel data analysis - Muhammad Fahrur Rozi (Nur Science Institute, 2025)
This study aims to examine the impact of Economic Growth, Open Unemployment Rate, Regional Minimum Wage, and Human Development Index on poverty levels within the Barlingmascakeb Region (Banjarnegara, Purbalingga, Banyumas, Cilacap, and Kebumen) during the period 2019–2023. A quantitative approach is employed using panel data regression analysis with the Fixed Effect Model (FEM). The study relies on secondary data sourced from the Central Bureau of Statistics of Indonesia. The findings reveal that collectively, the independent variables significantly influence the dependent variable. However, in partial analysis, Economic Growth and Unemployment exhibit a positive but statistically insignificant effect on poverty. In contrast, the Regional Minimum Wage has a positive and significant influence on poverty levels. Meanwhile, the Human Development Index demonstrates a significant negative effect on poverty. Additionally, the coefficient of determination test indicates that the independent variables collectively account for a substantial proportion of the variation in poverty levels. The integration of local cultural elements into visual design aims to strengthen students’ cultural literacy, as recommended in local wisdom-based learning.